Construction of Ag/g-C3N4 composites with uniform-sized Ag nanoparticles and the application for sulfisoxazole degradation in the presence of visible radiation. Issue 5 (October 2020) - Song, Yali; Gao, Shanshan; Tian, Jiayu; Zhang, Hongzhong
Graphical abstract: Highlights: Additional PVP can control Ag size and enhance optical property of Ag/g-C3 N4 . Visible-light photocatalytic activity of SIX by Ag/g-C3 N4 was improved. Intermediates and transformation pathways in photodegradation process were revealed. Ag/g-C3 N4 showed excellent photocatalytic activity of SIX in real water matrices. Abstract: To ensure efficient removal of SIX, Ag/g-C3 N4 with uniform-sized Ag nanoparticles was synthesized. With the employment of poly vinylpyrrolidone in synthesis process, Ag sizes were controlled and the photoabsorption ability of Ag/g-C3 N4 for visible-light was improved. In comparison with g-C3 N4, the degradation kinetic constant of SIX was increased by 1.75 times when Ag content was optimized (5 wt.% in this work, i.e. Ag/g-C3 N4 -5). The primary species for SIX degradation by Ag/g-C3 N4 -5 were holes and ·O2 − in the presence of visible radiation. Besides, the intermediate products generated in reaction processes were identified and the transformed pathways were proposed in photocatalytic process of SIX by Ag/g-C3 N4 -5, including the rupture of the chemical bond between S and benzene ring, the rupture of SN bond, the hydroxylation and nitration of benzene ring. Finally, the photocatalytic degradation of SIX in two authentic water bodies revealed the efficient removal of SIX can still be realized by Ag/g-C3 N4 -5.